'We go back to the land': processes of re-peasantisation in Araponga, Brazil. Issue 3 (19th March 2018) - van den Berg, Leonardo; Hebinck, Paul; Roep, Dirk
Abstract : This contribution draws on original data relating to a land settlement case in Araponga, an administrative area in Minas Gerais, Brazil. The settlement of the land and subsequent building of robust, more self-dependent, land-based livelihoods have followed a joint experimentation trajectory in which the agro-ecologicalisation of agrarian production practices to regenerate and enrich the resource base has been coupled with effective institutional reform and the creation of a favourable institutional setting. Key to this grassroots transformation process has been the enrolment of various strategic actors in a collaborative support network by a mediating change agent. The paper argues that the Araponga case represents a particular expression of re-peasantisation. The Araponga project has evolved without the involvement of landless peoples' social movements such as the Movimento dos Trabalhadores Rurais Sem Terra (MST). This has been crucial to its character and impact.